WHO European Childhood Obesity Surveillance Initiative: Impact of Type of Clothing Worn during Anthropometric Measurements and Timing of the Survey on Weight and Body Mass Index Outcome Measures in 6–9-Year-Old Children - Wijnhoven, Trudy M.A. (2017)
Background. The World Health Organization European Childhood Obesity Surveillance Initiative (COSI) conducted examinations in 6–9-year-old children from 16 countries in the first two rounds of data collection. Allowing participating countries to adhere to their local legal requirements or adapt to other circumstances required developing a flexible protocol for anthropometric procedures. Objectives. (1) Review intercountry variation in types of clothing worn by children during weight and height measurements, clothes weight adjustments applied, timing of the survey, and duration of data collection; (2) assess the impact of the observed variation in these practices on the children’s weight or body mass index (BMI) outcome measures. Results. The relative difference between countries’ unadjusted and clothes-adjusted prevalence estimates for overweight was 0.3–11.5%; this figure was 1.4–33.3% for BMI-for-age Z-score values. Monthly fluctuations in mean BMI-for-age Z-score values did not show a systematic seasonal effect. The majority of the monthly BMI-for-age Z-score values did not differ statistically within a country; only 1–3 monthly values were statistically different within some countries. Conclusions. The findings of the present study suggest that the built-in flexibility in the COSI protocol concerning the data collection practices addressed in the paper can be kept and thus do not necessitate a revision of the COSI protocol.